A cross-system approach for multimedia services with IP multicast in 4G networks - Gomes, Diogo Nuno Pereira
The increased demand for multimedia services by mobile end users in recent years have driven both Broadcast and Wireless Network operators to develop new systems and architectures for the deployment of such services. The proposed solutions are nonetheless limited either in terms of QoS or Capabilities to deliver new interactive services. This paper highlights strengths and drawbacks of the existing technologies in terms of QoS, Security and Mobility. In order to fill the gap between current solutions we propose a new architecture that builds itself on the synergies created by a heterogeneous network made of existing delivering technologies, such as 3GPP/MBMS and DVB, where services can be delivered to end-users in the most appropriate way for end-users and operators alike. A prototype implementation is further described.